Designing and 3d Printed Pla Based Implant Used in Treatment For Unilateral Vocal Cord Paralysis - Ciftci, Fatih; Ayan, Sumeyra; Ustundag, Cem Bulent (Kerim Çetinkaya, 2021)
This study aims to develop and demonstrate a new method of creating polymeric vocal cord (VC) models via 3D printing to reduce model production time, increase sound efficiency, and lay the groundwork for future models using more realistic geometric and functional biomaterials. For this purpose, it is to produce a poly (lactic acid) (PLA) based VC implant using a 3D printer as a special design according to the patient's vocal structure. In this study, VC 3D PLA implant (VC3DPLAI), VC stretch piece (measured = 35 mm length), fixed to thyroid cartilage VC (cartilage length = 12 mm) and titanium (Ti64) springs pieces are expected to be produced as a patient-specific implant It is composed of three different biomechanical designs. When you compare this implant with other biomaterials, the VC3DPLAI provides personal convenience compared to complex models and allows unlimited time-cost competition.
Keywords: 3D Printer; Biomaterials; Implants; Poly (lactic-acid); Thyroplasty; Vocal Cord Paralysis